Wood density variations of E. urophylla clone among growth sites are related to climate - Almeida, Maria Naruna Felix; Vidaurre, Graziela Baptista; Louzada, José Luis Penetra Cerveira; Pezzopane, José Eduardo Macedo; Rocha, Sofia Maria Gonçalves; Câmara, Ana Paula; Oliveira, Jean Carlos Lopes; Alvares, Clayton Alcarde [UNESP]; Campoe, Otávio Camargo (Canadian Science Publishing, 2023)
The Eucalyptus genus is extensively planted in Brazil for industrial use, and with the expansion of forest frontiers and climate changes, studies are needed on how these changes affect wood density (WD). The aim of this study was to evaluate the effect of some climate variables on WD of an Eucalyptus urophylla clone for a 4-5 year period. WD from trees collected in 12 sites were evaluated. Five growth rings were identified using a magnifying glass, X-ray densitometry, and forest inventory. WD was correlated with temperature (T), precipitation (P), soil water deficit, ring width, and current annual increment. There was no variation in WD in the first 20 months among sites. From that age on, WD was mainly correlated with T (r > 0.6). The 1 ◦C increase in T resulted in a WD reduction of 0.014 g cm−1, and increases of 10 m3 ha−1 in the final volume were related to an increase of 0.004 g cm−1 in WD. Researchers and managers should continue to put efforts into broad experimental networks Highlights The influence of climate on E. urophylla wood density was greater after the third year of growth. The mean air temperature was the best correlated climatic variable with E. urophylla wood density. The cross-site climatic gradient was more important in wood density variation of E. urophylla than the variability among the years.
Keywords: annual growth; climate conditions; densitometry; forest expansion; wood quality